Analysis and Design of UI/UX Sepran Application Using Design Thinking Method - Hidayah, Annisa Nur; Arifa, Amalia Beladinna (Journal of INISTA, 2024)
Abstract Finance is something that must be thought about from a broader perspective. A low level of financial literacy can result in individuals making financial decisions using only speculation, not according to financial analysis sourced from historical data. If the decision taken turns out to be wrong or inappropriate, it will have an impact on financial health in the future. This statement can be overcome by using several financial management applications that provide features to view historical financial expenses and income in a certain period, one of which is the Sepran application: Expenses Manager. However, this Sepran application still has several shortcomings, such as not being able to connect to an e-wallet so that it can only be input manually, the font size and some icons that still look small, and the colours used in expenses. From these problems, a redesign of the Sepran application will be carried out using the design thinking method approach and the System Usability Scale (SUS) to measure the success rate of the designed interface. Design thinking has 5 stages, namely Empathize, Define, Ideate, Prototype, and Test. The first stage, empathize, is the stage of extracting problems. Define is the stage of defining problems, and ideate is the stage of determining ideas from problems that have been defined at the ideate stage. Furthermore, the prototype is a stage where ideas that have been determined at the ideate stage are implemented into low- and high-fidelity designs. The last is the test stage, where this stage will test using SUS through a prototype to get feedback and find out whether the design objectives have been achieved. The purpose of this research is to redesign the Sepran application to meet user needs and analyze the success rate of the interface using SUS. The results obtained an average score of 93.25 and a grade of A. This score indicates that the redesign of the Sepran application is in accordance with user needs.